2017
DOI: 10.1038/ncomms13759
|View full text |Cite
|
Sign up to set email alerts
|

Bi- and uniciliated ependymal cells define continuous floor-plate-derived tanycytic territories

Abstract: Multiciliated ependymal (E1) cells line the brain ventricles and are essential for brain homeostasis. We previously identified in the lateral ventricles a rare ependymal subpopulation (E2) with only two cilia and unique basal bodies. Here we show that E2 cells form a distinct biciliated epithelium extending along the ventral third into the fourth ventricle. In the third ventricle floor, apical profiles with only primary cilia define an additional uniciliated (E3) epithelium. E2 and E3 cells' ultrastructure, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(113 citation statements)
references
References 49 publications
5
108
0
Order By: Relevance
“…This question is controversial. Scanning 221 and transmission 7,9,62,222 electron microscopy, and in block immunocytochemistry, have shown that some tanycytes are endowed with a single 9+0 cilium, similar to those reported for the NSC present in the sub- Glutamate is known to be neurotoxic at elevated concentrations and plays an important role in brain injury following acute and chronic brain insults. Therefore, the BBB is impermeable to glutamate, even at high concentrations.…”
Section: Would All α2-tanycytes Keep Such Potency?supporting
confidence: 70%
See 3 more Smart Citations
“…This question is controversial. Scanning 221 and transmission 7,9,62,222 electron microscopy, and in block immunocytochemistry, have shown that some tanycytes are endowed with a single 9+0 cilium, similar to those reported for the NSC present in the sub- Glutamate is known to be neurotoxic at elevated concentrations and plays an important role in brain injury following acute and chronic brain insults. Therefore, the BBB is impermeable to glutamate, even at high concentrations.…”
Section: Would All α2-tanycytes Keep Such Potency?supporting
confidence: 70%
“…62 The cilia occupied the lumen of a deep invagination of the plasma membrane. Some cells were seen to project one or two 9+2 cilia.…”
Section: Cell Bodymentioning
confidence: 99%
See 2 more Smart Citations
“…This diversity is perhaps nowhere on more prominent display than in C. elegans. In addition to the single cilia that are similar to those found on most mammalian cells, C. elegans neurons (e.g., ADF and ADL neurons) can possess pairs of cilia, at least superficially similar to the paired cilia found on mammalian tanycytes [1417]. Even more impressively, other C. elegans neurons possess cilia with elaborate membrane extensions that have been compared to wings (AWA, AWB, AWC neurons), bags (BAG) or flaps (FLP).…”
Section: Different Types Of Cilia Exhibit Different Membrane Morpholomentioning
confidence: 99%